GLOBAL MIGRATION SEBAGAI SOLUSI JEPANG DALAM MENGHADAPI AGING POPULATION MELALUI THE IMMIGRATION CONTROL AND REFUGEE RECOGNITION ACT - Fitri Sholihin (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2022)
Aging population is a serious challenge for the Japanese Government. The increasing proportion of the elderly in the population and slower population growth are the basic reasons behind Japan's aging population. The challenges with the aging population have affected Japan's economic performance by increasing the burden and social security benefits. The Japanese government said that this challenge had become a